The Physical Properties of Fig (Ficus carica L.) as a Function of Moisture Content and Variety - Razavi, Seyed M. A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
Some physical and aerodynamic properties of two commercial figs (Ficus carica L.), namely, open and close figs, as a function of variety and moisture content were investigated. The results showed that for close figs, length, width, height, terminal velocity, geometric arithmetic mean diameters and surface area increased with increasing moisture content, whereas these parameters for open fig decreased. In both open and close figs, unit mass, true volume, bulk density and static angles of friction surfaces increased, while particle density and porosity decreased with increasing moisture content. For open fig, rolling resistance had increasing linear behavior and for close fig, decreasing nonlinear behavior with moisture content. Filling angle of repose of close and open dried figs were 26.38° and 25.81°, respectively, at 34.60% moisture content. The relationship between measurement properties and moisture content were represented by regression equations which have a high determination coefficient and could be used for prediction of all properties for processing and design.